Perilaku Impulse Buying Pengguna Shopee Masa Pandemi Covid-19 - Kevin Aurelius Wijaya; Kartika Imasari Tjiptodjojo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The emergence of the Covid-19 era has affected various aspects of people's lives where this also influences the consumer behavior of the community which consists of the variables of viral marketing, impulse buying, and customer trust. This study aims to determine the impact of changes in consumer behavior during the Covid-19 pandemic. The data collection technique was carried out using non-probability sampling with a purposive sampling technique and distributed through questionnaires through social media. The population used is active users of social media and the Shopee application in the city of Bandung. The targeted number of respondents is 115 respondents. The path analysis technique is used as a data exposure technique and is processed with the help of the SPSS application. This study reveals the results where viral marketing has an effect on impulse buying and customer trust, while customer trust does not affect impulse buying, and also customer trust does not mediate the indirect effect of viral marketing on impulse buying.